2016
DOI: 10.2174/1567205013666160129095508
|View full text |Cite
|
Sign up to set email alerts
|

Increased Epileptiform EEG Activity and Decreased Seizure Threshold in Arctic APP Transgenic Mouse Model of Alzheimer's Disease

Abstract: Several Alzheimer model mice carrying transgenic amyloid precursor protein (APP) with the Swedish mutation have been reported to exhibit spontaneous seizures and/or increased epileptiform EEG activity. The primary cause for the epilepsy phenotype is still under debate. In contrast to mice with APPswe mutation that develop extracellular amyloid plaques, mice with APP Arctic mutation (E693G) have no bias toward β-secretase cleavage and display intracellular amyloid deposits but not plaques. We conducted a system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 0 publications
5
24
0
Order By: Relevance
“…Consistently with the aforementioned evidence, different mice models that overexpress APP also show hyperexcitation in individual neurons, interictal spikes, and spontaneous seizures in cortical and hippocampal networks . One of them, the APdE9 transgenic mouse model, generated by crossing transgenic mice expressing the APP human protein and the human PS1‐dE9 (deletion of exon 9), has been reported to have spontaneous seizures and increased neuronal excitability .…”
Section: Amyloid‐β Pathway In Acquired Epilepsysupporting
confidence: 53%
“…Consistently with the aforementioned evidence, different mice models that overexpress APP also show hyperexcitation in individual neurons, interictal spikes, and spontaneous seizures in cortical and hippocampal networks . One of them, the APdE9 transgenic mouse model, generated by crossing transgenic mice expressing the APP human protein and the human PS1‐dE9 (deletion of exon 9), has been reported to have spontaneous seizures and increased neuronal excitability .…”
Section: Amyloid‐β Pathway In Acquired Epilepsysupporting
confidence: 53%
“…25 In addition, increased β-site cleavage products and epileptic seizures were observed in APPSWE mice that were developed to simulate extracellular Aβ aggregation. 26 All of these findings support the notion that ADAM10 could protect against epileptic seizures in AD.…”
Section: Epileptic Phenotypes Of Adam10 In Transgenic Modelssupporting
confidence: 62%
“…Roberson et al, 2007 ); briefly, J20 mice cross-bred to mice deficient in tau (tau KO) showed levels of hippocampal activity that were similar to those displayed by WT mice. Earlier authors proposed that the hyperexcitability observed in J20 mice results from Aβ -induced Fyn-mediated NMDA receptor activation (Ittner et al, 2010 ; Roberson et al, 2011 ) this interpretation is supported by reports that most APP transgenic mice exhibit spontaneous seizures and/or increased epileptiform EEG activity (Ziyatdinova et al, 2016 ).…”
Section: Discussionmentioning
confidence: 90%